A SOM‐based analysis of the drivers of the 2015–2017 Western Cape drought in South Africa. (26th August 2020) - Odoulami, Romaric C.; Wolski, Piotr; New, Mark
Abstract: The multi‐year (2015–2017) drought in the South West of the Western Cape (SWC) caused a severe water shortage in the summer of 2017–2018, with damaging impacts on the local and regional economy, and Cape Town being in the news one of the first major cities to potentially run out of water. Here, we assess the links between the rainfall deficits during the drought and (a) large scale circulation patterns, (b) moisture transport, and (c) convective available potential energy (CAPE). We used self‐organising maps (SOM) analysis to classify daily ERA‐interim 850 hPa geopotential height for the period 1979–2017 (March–October) into synoptic types. This allowed us to identify the dominant synoptic states over Southern Africa that influence the local climate in the area affected by the drought. The results show that (a) the frequency of nodes with rain‐bearing circulation types decreased during the drought; (b) the amount of rain falling on days that did have rain‐bearing circulation types was reduced, especially in the shoulder seasons (March–May and August–October); (c) the rainfall reduction was also associated with anomalously low moisture transport, and convective energy (CAPE), over SWC. These results add to the existing knowledge of drivers of the Cape Town drought, providing an understanding of underlying synoptic processes. Abstract : Applying the self‐organizing maps (SOMs) to classify daily 850 hPa geopotential height into circulation types over Southern Africa revealed decreases (increases) in the frequency of wet (dry) circulation types during the drought period (2015–2017). Additionally, rainfall frequency and intensity decreased when wet circulation conditions were present but, increased (frequency) or were near normal (intensity) in nodes with dry circulation types, due to reduced moisture transport and reduced convective available potential energy.